2021
DOI: 10.1177/17562864211019574
|View full text |Cite
|
Sign up to set email alerts
|

Long-term disability trajectories in relapsing multiple sclerosis patients treated with early intensive or escalation treatment strategies

Abstract: Background and aims: No consensus exists on how aggressively to treat relapsing–remitting multiple sclerosis (RRMS) nor on the timing of the treatment. The objective of this study was to evaluate disability trajectories in RRMS patients treated with an early intensive treatment (EIT) or with a moderate-efficacy treatment followed by escalation to higher-efficacy disease modifying therapy (ESC). Methods: RRMS patients with ⩾5-year follow-up and ⩾3 visits after disease modifying therapy (DMT) start were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 32 publications
1
44
0
1
Order By: Relevance
“…Among first-line pharmacotherapies in MS is glatiramer acetate; however, the response rate is not greater than 55% due to variability in genetic polymorphisms [72]. Recent studies have demonstrated that long-term disability outcomes tend to be better in MS patients who are treated early with "high-efficacy" medicines including the anti-CD20 monoclonal antibodies rituximab (Rituxan) and ocrelizumab (Ocrevus) targeting B cells, the anti-α4β1 integrin monoclonal natalizumab (Tysabri), the type II topoisomerase inhibitor mitoxantrone (Novantrone), the sphingosine-1-phosphate receptor modulator fingolimod (Gilenya) [73], the monoclonal anti-CD52 alemtuzumab (Campath, Lemtrada) targeting mature lymphocytes, and the purine analogue cladribine (Mavenclad) that delivers "intensive" immune intervention, as compared to patients who are treated with "moderate-efficacy" medications for one or more years prior to "escalation" to the high-potency agents [74,75]. Adverse effects are more complex for the "high-efficacy" treatment strategies and include increased risks of serious infections and cancers associated with immunosuppression, autoimmune diseases associated with immunomodulation, cardiotoxicity, hepatotoxicity, and gastrointestinal and neuropsychiatric disorders [76,77].…”
Section: Therapeutic Challenges and Biomarker Research In Msmentioning
confidence: 99%
“…Among first-line pharmacotherapies in MS is glatiramer acetate; however, the response rate is not greater than 55% due to variability in genetic polymorphisms [72]. Recent studies have demonstrated that long-term disability outcomes tend to be better in MS patients who are treated early with "high-efficacy" medicines including the anti-CD20 monoclonal antibodies rituximab (Rituxan) and ocrelizumab (Ocrevus) targeting B cells, the anti-α4β1 integrin monoclonal natalizumab (Tysabri), the type II topoisomerase inhibitor mitoxantrone (Novantrone), the sphingosine-1-phosphate receptor modulator fingolimod (Gilenya) [73], the monoclonal anti-CD52 alemtuzumab (Campath, Lemtrada) targeting mature lymphocytes, and the purine analogue cladribine (Mavenclad) that delivers "intensive" immune intervention, as compared to patients who are treated with "moderate-efficacy" medications for one or more years prior to "escalation" to the high-potency agents [74,75]. Adverse effects are more complex for the "high-efficacy" treatment strategies and include increased risks of serious infections and cancers associated with immunosuppression, autoimmune diseases associated with immunomodulation, cardiotoxicity, hepatotoxicity, and gastrointestinal and neuropsychiatric disorders [76,77].…”
Section: Therapeutic Challenges and Biomarker Research In Msmentioning
confidence: 99%
“…EIT was significantly associated with lower disability progression measured by mean annual EDSS change compared to baseline value in all time points, including at 5 and 10 years. This effect not only persisted but continued to increase over time despite all patients in the escalation group being escalated to a higher-efficacy DMT [61].…”
Section: The Importance Of Long-terms Outcomes Analysis Of the Compar...mentioning
confidence: 92%
“…Recent evidence from several observational studies, suggest that EIT provides a greater benefit than escalation treatment in decreasing the risk of developing SPMS and disability accrual at least in the medium-long term of 5 to 10 years [43,[58][59][60][61][62].…”
Section: The Importance Of Long-terms Outcomes Analysis Of the Compar...mentioning
confidence: 99%
“…When it comes to defining the candidates for higher efficacy treatments Bayas et al [5] restrict this option to treatment failures of "category 1" compounds andin treatment naïve patients -to "probably highly active" disease that they define following recommendations from a recent workshop about "aggressive" MS [8]. Wiendl et al [6] suggest a more open approach to early high efficacy treatment, being encouraged by accumulating evidence from several registry based observational studies supporting the benefits of early high efficacy treatments [9,10]. Both author groups acknowledge that results of controlled prospective studies comparing the benefit-risk balance of the early high efficacy treatment approach ("hit hard and early") versus an escalation approach are still pending.…”
Section: Ludwig Kapposmentioning
confidence: 99%
“…If an optimal control of disease activity and progression is our goal only concerns about risk and tolerability can prevent from using the most effective treatment options. The manageable risk and convenience profile emerging from long term extensions of large controlled studies [11][12][13] and from systematic follow up in real world settings [9,10] for some of the high efficacy treatments, namely S1P modulators, anti-CD20 monoclonal antibodies and natalizumab (in JC virus negative patients and probably even more with extended interval dosing) [14] alleviate such concerns more and more.…”
Section: Ludwig Kapposmentioning
confidence: 99%